The Impact of Weak Marine Debris Governance on the Increased Environmental Insecurity in Southeast Asia - Sudirman, Arfin; Idris, Idris; Siswandi, Achmad Gusman; Adolf, Huala; Fadilah, Edta Muhammad; Maulana, Mursal; Hakiki, Falhan (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Southeast Asian region is home to five countries that are included in the list of the top 10 countries that produce marine debris in the world. Although there are a lot of efforts to handle the situation through the creation of marine debris governance in the region such as the ASEAN Regional Action Plan, not much has changed. This article aims to determine what Is the cause of weak marine debris governance and how it is impacted the increasing environmental insecurity In Southeast Asia based on the concept of policy harmonization and environmental security according to John Barnett's thinking which divides its meaning into three forms, namely changes in the environment, threats to national security, human security, and triggers for conflict. The research method used is descriptive qualitative research. Researchers found that weak marine debris governance formed as the result of a lack of policy harmonization between countries in the region regarding marine debris pollution and that environmental degradation that ensued had implications for the scarcity of marine resources, which is one of the main economic driving sectors for countries in the region and the possibility to contribute to fisheries conflicts that often occur in the South China Sea, which poses a threat to the national security of the surrounding countries. In addition, this environmental issue also creates human insecurity in the form of economic losses for coastal communities as well as health hazards for the human body.